2020
DOI: 10.1136/tobaccocontrol-2019-055232
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the price elasticity for cigarette and chewed tobacco in Pakistan: evidence from microlevel data

Abstract: BackgroundWhile there is a large literature on the magnitude of price elasticity of cigarette demand, less is known about the same for chewed tobacco. Moreover, the studies on cigarette demand in Pakistan tend to ignore the heterogeneity in the smoking behaviour. This study estimates price elasticity for cigarette and chewed tobacco demand across different income groups, provinces and regions; and use these coefficients for simulating Pakistan’s tax policy and its impact on revenue and health outcomes.MethodDe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…group-level disaggregation of the cost of tobacco-attributable disease burden, 15 none of the existing studies help. This paper communicates Pakistan's first ever estimate of the economic cost of smoking-attributable cancer, CVD and respiratory disease from a nationally representative survey of smokers and non-smokers in the country for the year 2019.…”
Section: Original Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…group-level disaggregation of the cost of tobacco-attributable disease burden, 15 none of the existing studies help. This paper communicates Pakistan's first ever estimate of the economic cost of smoking-attributable cancer, CVD and respiratory disease from a nationally representative survey of smokers and non-smokers in the country for the year 2019.…”
Section: Original Researchmentioning
confidence: 99%
“…These findings also support the arguments made in some recent studies. For example, Nayab et al 15 and Saleem and Asif 24 reported household tobacco expenses are higher in the rural areas and among the lower income groups and argued that tobacco crowds out investment in human capitals in Pakistan and pushes households into a vicious cycle of poverty. Given that tobacco consumption is highly price elastic, suggesting price increase would reduce demand significantly, taxing tobacco to WHO standards and ensuring tax pass through to consumer prices of cigarettes would simultaneously improve economic and health outcomes.…”
Section: Original Researchmentioning
confidence: 99%
“…The study that analyses the price elasticity by income groups in Argentina9 shows that price increase by 10% reduces the cigarette consumption by 2.8% and that wealthier individuals are more price sensitive, in absolute value, than the poorer ones with respect to consumption but they are less price sensitive with respect to prevalence. The studies from Thailand and Moldova also show that the cigarette consumption in low-income socioeconomic groups is more responsive to changes in the price than those in high-income socioeconomic groups,10 11 while the study from Pakistan reveals that only smokers belonging to the low-income group are price sensitive 12…”
Section: Introductionmentioning
confidence: 97%
“…The studies from Thailand and Moldova also show that the cigarette consumption in low-income socioeconomic groups is more responsive to changes in the price than those in high-income socioeconomic groups, 10 11 while the study from Pakistan reveals that only smokers belonging to the low-income group are price sensitive. 12 This paper examines price and income elasticity of the cigarette demand by three income groups in B&H. Reducing the demand for cigarettes can be reached by decreasing the prevalence of smoking or smoking intensity. Thus, we use a two-part model that is based on logistic regression to estimate prevalence elasticity and the Deaton demand method to estimate the elasticity intensity.…”
Section: Introductionmentioning
confidence: 99%
“…4 The WHO estimates that 32.4% males and 5.7% females in Pakistan are current tobacco users. 5 Shisha, a form of smoked tobacco, has also become a growing trend among the Pakistani youth and as per a study reported from Karachi in 2008, regular shisha consumers included 43% males and 11% female university students. 6 Approximately 8% of the population in the country also consumes smokeless tobacco in various forms.…”
mentioning
confidence: 99%